Posttraumatic growth and related factors among relatives, caring for cancer patients. Systematic review (Part 1) - A. M. Shishkova; V. V. Bocharov; E. S. Tsygankova; E. A. Granovskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Caring for cancer patients can have not only negative impact on the informal caregivers, but can also be a source of positive personality transformations in the challenging situation associated with cancer. Aim: identification and synthesis of data on posttraumatic growth (PTG) and socio-demographic, clinical and psychological factors associated with PTG in relatives, caring for patients with cancer. Methods: The review was conducted according to the statement of the PRISMA guidelines. The review used 2 search strategies: systematic electronic search in databases (Pubmed, Google Scholar, Cochrane, EBSCO, SAGE journals и eLIBRARY), manual search of articles in references lists of eligible articles. Results: a total of 23 studies were included in the review. The total amount of relatives and loved ones, caring for cancer patients was 5140. The average age of respondents was 52,2 (SD = 10,77) years. The majority of those surveyed were female - 58% and were spouses/partners of patients (52%). PTG among cancer patients' relatives is a universal phenomenon that occurs in a wide variety of socio-cultural populations and ethnic groups. The Posttraumatic Growth Inventory (PTGI) is the most popular tool used for assessing PTG in the analyzed studies. Conclusion: there is a gap in domestic research on PTG among cancer patients' informal caregivers. The implementation of the PTG in to the clinical practice will help significantly expand the possibility of providing specialized psychological assistance to them.